Effects of front suspension on mountain bike impact performance - Levy, M.; Smith, G. A. (3rd International Conference on the Engineering in Sport June, 2000 in Sydney, Australia, 2000)
This project assessed impact performance of mountain bikes through measurement of horizontal force and impulse with four fork conditions. Results: Clear relations of force and impulse to speed existed for each fork condition with correlations ranging from about ± 0.5 to 0.9. While the increases of peak force with speed wereexpected, impulse consistently decreased with speed. Thus speed changes due to bump impact decreased as speed increased. ANCOVA was used to compare the forks using speed as a covariate. As expected, considerably greater force and impulse was characteristic of the rigid forks (p < .001). The suspension forks attenuated forces by 20 - 30% compared to the rigid forks. Small but significant differences were observed between suspension forks (p<.01). The simplest designed suspension (elastomer), provided greatest peak force attenuation but at the same time produced the greatest braking impulse and would slow the bike more than the other suspension forks. Fork stiffness settings were not tested in this project as each was set at mid-range. Adjustments to each of the suspensions could conceivably improve performance. Thus despite significant statistical differences in the three suspension forks, conclusions about performance should await further tests involving stiffness adjustments as well as tests involving varying bump configurations.